Genomic imbalance in subjects with idiopathic intellectual disability detected by multiplex ligation-dependent probe amplification - MOHAN, SHRUTHI; VENKATESAN, VETTRISELVI; PAUL, SOLOMON FD; KOSHY, TEENA; PERUMAL, VENKATACHALAM (Journal of genetics, 2016)
Intellectual disability (ID) is a complex disorder with heterogeneous aetiology. The prevalence rate is about 23% worldwide. The cause of ID in at least half of the affected population is unclear and is reported as idiopathic ID. In addition to chromosomal abnormalities (Rio et al. 2002) and single gene mutations (Curry et al. 1997), segmental aneusomy caused by genomic rearrangements that may occur throughout the genome is implicated as a signicant aetiological factor.